2018
DOI: 10.1021/acsaem.8b01118
|View full text |Cite
|
Sign up to set email alerts
|

All-Nanoparticle SnO2/TiO2 Electron-Transporting Layers Processed at Low Temperature for Efficient Thin-Film Perovskite Solar Cells

Abstract: Solution processed metal halide perovskite materials have revealed outstanding optoelectronic features that make them uniquely suited for photovoltaic applications. Although a rapid progress has led to performances similar to inorganic thin film technologies, the fabrication method of some of the most widely used electron selective layers, based on either mesoporous architectures or high annealing temperatures, may limit yet a future large scale production. In that regard, planar perovskite solar cell configur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 54 publications
1
32
0
Order By: Relevance
“…This can easily be seen from Equation , in which the A ( E , θ ) terms in the numerator and denominator would rub out, leaving a V oc,rad expression depending only on the thickness‐independent S ( E ) and B ( E ). The decrease in V oc,rad with the perovskite thickness can be qualitatively attributed to an increased optical absorption mostly in the bandgap region, which implies a decrease in the perovskite effective optical bandgap . In addition to this decreasing trend, one observes an oscillatory pattern that likely results from optical interference.…”
Section: Oc and Qy Of Complete Perovskite Solar Cellsmentioning
confidence: 91%
See 1 more Smart Citation
“…This can easily be seen from Equation , in which the A ( E , θ ) terms in the numerator and denominator would rub out, leaving a V oc,rad expression depending only on the thickness‐independent S ( E ) and B ( E ). The decrease in V oc,rad with the perovskite thickness can be qualitatively attributed to an increased optical absorption mostly in the bandgap region, which implies a decrease in the perovskite effective optical bandgap . In addition to this decreasing trend, one observes an oscillatory pattern that likely results from optical interference.…”
Section: Oc and Qy Of Complete Perovskite Solar Cellsmentioning
confidence: 91%
“…The decrease in V oc,rad with the perovskite thickness can be qualitatively attributed to an increased optical absorption mostly in the bandgap region, which implies a decrease in the perovskite effective optical bandgap. [1,4,27] In addition to this decreasing trend, one observes an oscillatory pattern that likely results from optical interference. This clearly demonstrates the importance of performing calculations taking into account coherent effects, angle dependence, and a realistic solar cell structure with realistic layer thicknesses and energy-dependent dielectric functions.…”
Section: Measured Qy and V Oc And Full-wavevector Generalized Detailementioning
confidence: 94%
“…The performances of different ML algorithms for the prediction of the PCE of PSCs are shown in Table 1. Due to the complexity of the reported experimental values (for example, in our dataset, for solar cells with E g = 1.5 eV, ΔH = 0.15 eV, and ΔL = 0.2 eV, PCE could either be 20.5% [35] or 15.2% [36] ), all the RMSE values were not very small. But among all the algorithms, the ANN and RF behaved the best for both true bandgap and predicted bandgap due to their smallest RMSE values.…”
Section: Perovskite Solar Cell Designmentioning
confidence: 99%
“…It was found that the heterojunction SnO 2 /TiO 2 gradient as a driving force could promote the charge transport from the perovskite photoactive layer into the ETL. However, Martinez‐Denegri et al [ 240 ] fabricated several tens of nanometer‐thick bilayers SnO 2 /TiO 2 as an ETL and applied it into translucent PSCs. The higher coverage of the ITO substrates would improve the average efficiency of planar structure translucent devices.…”
Section: Modification Of Semiconductor Oxidementioning
confidence: 99%